Relevansi Islamisasi Sains terhadap Dikotomi Ilmu Pengetahuan pada Al-Qur’an - Muthiiatun Muthiiatun; Said Agil Husen Al-Munawar; M. Ziyadul Haq (Departement of Mathematics Education, 2024)
In the development of modern science, it is seen to separate the elements of religious values ​​from science in general which are logical and realistic, resulting in a dichotomy of knowledge. In addition, the emergence of a dichotomy of knowledge resulted in the dualism of education. Therefore we need an idea known as the Islamization of science as a form of solution to describe the dichotomy of knowledge. In this study, the authors raised the results of the thoughts of the two figures who gave rise to ideas about the Islamization of science, namely Syed Muhammad Naquib al-Attas and Ismail Raji al-Faruqi. According to al-Attas, the Islamization of science prioritizes the subject first, namely humans by purifying their souls from mythical, magical, occult and secular elements, then incorporating Islamic elements into relevant science. Meanwhile, al-Faruqi argued that the Islamization of science was emphasized more on its object, namely the discipline of science. The results of the study concluded that the Qur'an is the main source of reference in science where there is no separation between religious values ​​and science in general. Even between the two of them are related and related to each other. With the efforts of the Islamization of science movement, it is hoped that the problem of the scientific dichotomy between religious and modern sciences can be integrated and can be integrated into the educational process.